Archaeology of the Jesuit Missions in the Lake Ṭana Region: Review of the Work in Progress - Fernández, Víctor M.; Martínez D'Alòs-Moner, Andreu; de Torres, Jorge; Cañete, Carlos (Aethiopica, 2012)
The Jesuit mission in Ethiopia, which extended from 1557 to 1632, produced important architectonic constructions. Most of these constructions were erected in the provinces of Däm